Strategic integration of human resource management and marketing in the digital business era: A systematic literature review - Suriono, Hadi; Bakti, Surya (Priviet Social Sciences Journal, 2025)
This study explores the convergence of human resource management (HRM) and marketing within the context of digital transformation by employing a systematic literature review (SLR) approach to synthesize findings from 57 high-quality peer-reviewed articles published between 2010 and 2023. This review identifies key frameworks and technological enablers, such as digital readiness, CRM systems, AI, and cloud-based platforms that facilitate strategic alignment between HRM and marketing. Four major thematic areas have emerged: digital transformation frameworks, mediating roles of technology, integration benefits and challenges, and strategic recommendations. The results reveal that organizations integrating HRM and digital marketing are more likely to achieve enhanced organizational agility, customer satisfaction, and employee engagement. However, challenges such as cultural resistance, skill gaps, and data governance issues remain. This study contributes to the existing body of knowledge by offering a conceptual map of HRM marketing integration and presenting actionable insights for both scholars and practitioners in digital business transformation. Recommendations include fostering a digital-first culture, investing in continuous employee development, and deploying integrated digital infrastructure. Future research directions are proposed to empirically validate the reviewed frameworks and examine long-term integration outcomes.